Child’s Information Security in Digital Space of the Russian Federation - S. S. Dubov; V. V. Linkov; M. A. Karbainova (Российский технологический журнал, 2019)
Our time is the time of rapid technological development. The Internet is becoming available to everyone, and it is expanding its influence in various fields. In addition, the number of users who are using the Internet and who are active consumers of different content is increasing. But the rapid development of technology has created new security problems. New types of threats are emerging, attack techniques are improving. Criminals are now trying to find their «victim»not only in the real world, but also in the digital world. So, today special attention is given to the issue of ensuring the user’s information security and user’s security in the digital world. One of the most vulnerable age groups are children. That is why one of the most important issues is the issue of protecting a child in such an environment. This article is devoted to the problem of information security of children and adolescents in our country. The article describes the main problem of the child in such an environment. On one hand, the virtual activity of the child is the key to its successful education. But, on the other hand, there are risks and problems in the digital world, such as access to prohibited content, that can cause harm to the mental health of a child. This article describes vulnerabilities in the information environment of students and educational institutions, as well as ways to counter the described vulnerabilities.